A dictionary of epidemiology - Porta, Miquel S.; Greenland, Sander, 1951-; Hernán, Miguel; Silva, Isabel dos Santos; Last, John M., 1926- (Oxford quick reference., 2014)
This sixth edition of A Dictionary of Epidemiology -- the most updated since its inception -- reflects the profound substantive and methodological changes that have come to characterize epidemiology and its associated disciplines. Sponsored by the International Epidemiological Association, this book remains the essential reference for anyone studying or working in epidemiology, biostatistics, public health, medicine, or the growing number health sciences in which epidemiologic competency is now required. More than just a dictionary, this text is an essential guidebook to the state of the science.